1998
DOI: 10.1093/mutage/13.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Urinary mutagenicity on TA98 and YG1024 Salmonella typhimurium strains after a hamburger meal: influence of GSTM1 and NAT2 genotypes

Abstract: Mutagenicity on TA98 and YG1024 Salmonella typhimurium strains of pan-fried hamburger extracts and of 24 h post-meal urine from 32 non-smoking volunteers was evaluated. Each participant in the study was GSTM1 and NAT2 genotyped. After cooking the meat showed mutagenic activity (mean +/- SD) on strains TA98 and YG1024 of 114 +/- 129 and 1437 +/- 1536 net revertants/g respectively. Twenty three of 32 urine samples showed clear mutagenic activity (i.e. caused at least a doubling of the number of spontaneous rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
3
8
0
3
Order By: Relevance
“…Hamburger products have previously been reported as a major source of chemical food mutagens to consumers [38,61]. The results obtained in our study further reinforce this view, as two different lots of hamburgers examined were found to be mutagenic in all three assays in Salmonella TA 100 strain, with one of the lots (batch 2) being both directly and indirectly mutagenic in all three assays.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hamburger products have previously been reported as a major source of chemical food mutagens to consumers [38,61]. The results obtained in our study further reinforce this view, as two different lots of hamburgers examined were found to be mutagenic in all three assays in Salmonella TA 100 strain, with one of the lots (batch 2) being both directly and indirectly mutagenic in all three assays.…”
Section: Discussionsupporting
confidence: 89%
“…Sodium azide is a known direct mutagen in Salmonella TA 100 [36], whereas 2-aminoantracene is metabolically activated by mono-oxygenases of the CYP1A family in rat liver [37]. Likewise, benzo[ a ]pyrene requires metabolic activation for mutagenicity [38]. …”
Section: Methodsmentioning
confidence: 99%
“…Our subjects averaged 86 kg in weight, so a typical subject had an intake of ∼344,000 rev/day from high-temperature meat; Peters et al [17] reported 253,700 rev/day in a study with a similar protocol. Extracts from fried beef and sausage were 10 times more mutagenic in YG1024 than in TA98 (Table 1), confirming a previous study [19], and was likely due to activation of HCAs by acetyltransferase in YG1024. When based instead on meat-derived mutagenicity measured in strain YG1024, our subjects had an intake of ∼3,440,000 rev/day.…”
Section: Discussionsupporting
confidence: 85%
“…Five years after the discovery that cooked meat was mutagenic, Baker et al [1982] demonstrated that consumption of cooked meat resulted in mutagenic urine in humans. This observation has been confirmed and extended by others [Dolara et al, 1984;Hayatsu et al, 1985;Sousa et al, 1985;Baker et al, 1986;Ohyama et al, 1987a,b;Doolittle et al, 1989;Hayatsu and Hayatsu, 1993;DeMarini et al, 1997;Gabbani et al, 1998;Johansson et al, 1998;Murray et al, 2001;Pavanello et al, 2002]. With the exception of one study involving 32 subjects [Gabbani et al, 1998] and another involving 50 [Pavanello et al, 2002], these were small studies involving 3-21 subjects that examined variables such as the type of meat or cooking method as well as the kinetics of urinary mutagenicity.…”
Section: Introductionmentioning
confidence: 53%